2020
DOI: 10.1177/0898010120933123
|View full text |Cite|
|
Sign up to set email alerts
|

Altruism and the Difficult Patient

Abstract: Background For some nurses, providing altruistic care to difficult patients is a challenge, leading to the use of negative coping strategies such as anger or avoidance, leaving the nurse frustrated and patients feeling rejected. Yet other nurses can deal positively with difficult patients. Purpose To study how the stress of caring for difficult patients affects the level of altruism and use of negative coping strategies in their care and to find out what positive coping strategies and interventions could be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Details of the study characteristics are provided in Table 1. The 13 studies came from 12 different countries: Saudi Arabia (n = 1) (17), India (n = 2) (2, 13), Australia (n = 1) (4), Turkey (n = 1) (19), Mauritius (n = 1) (21), USA (n = 1) (22), Poland (n = 1) (23), Iran (n = 1) (24), Sweden (n = 1) (14), Kenya (n = 1), South Africa (n = 1), Thailand (n = 1) (25) and China (n = 2) (26,27). The year of publication ranged from 2012-2021.…”
Section: Search Outcomes and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of the study characteristics are provided in Table 1. The 13 studies came from 12 different countries: Saudi Arabia (n = 1) (17), India (n = 2) (2, 13), Australia (n = 1) (4), Turkey (n = 1) (19), Mauritius (n = 1) (21), USA (n = 1) (22), Poland (n = 1) (23), Iran (n = 1) (24), Sweden (n = 1) (14), Kenya (n = 1), South Africa (n = 1), Thailand (n = 1) (25) and China (n = 2) (26,27). The year of publication ranged from 2012-2021.…”
Section: Search Outcomes and Study Characteristicsmentioning
confidence: 99%
“…It was the core of the nursing profession or the basis for choosing nursing as a profession. More than half of the studies identified altruism as a personal or work value (4,14,17,21,22,25,26). Three studies perceived it as the professional equivalent to professional skills and as a reflection and representation of the level of expertise (13,19,27).…”
Section: Altruism In Nursingmentioning
confidence: 99%
See 2 more Smart Citations
“…Nursing has indeed long been linked to the meaning of vocation and altruism, where the need to help and care for others is considered one of the most salient attributes of the professions' identity (Carter 2014;Kenny 2010). Altruism is then associated with a genuine desire to alleviate another's suffering (Eley et al 2010), and to put the needs of others before one's own (Kubsch et al 2021). The concepts of vocation and altruism are still contrasted to professionalism and paid employment today (Slettmyr et al 2017).…”
mentioning
confidence: 99%